Paksaan Hukum dan Hak Kebebasan Beragama di Indonesia - Rizki, Muhamad (AHKAM, 2022)
Law and Religious Freedom, Religious Freedom means the rights of person to choose and confess a religion and belief. Religious freedom also perceived, by some people, as the right to choose whatever religion and belief, without considering the rights of others. However, religious freedom is limited by Constitution of 1945 and the regulations below it. Legal policy determines the need of law enforcement consistently aiming to ensure legal certainty, justice and truth, law supremacy and the respect towards human rights.